Osmotic pressure effects identify dehydration upon cytochrome c–cytochrome c oxidase complex formation contributing to a specific electron pathway formation. Issue 8 (29th April 2020) - Sato, Wataru; Hitaoka, Seiji; Uchida, Takeshi; Shinzawa-Itoh, Kyoko; Yoshizawa, Kazunari; Yoshikawa, Shinya; Ishimori, Koichiro
Abstract : In the electron transfer (ET) reaction from cytochrome c (Cyt c ) to cytochrome c oxidase (C c O), we determined the number and sites of the hydration water released from the protein surface upon the formation of the ET complex by evaluating the osmotic pressure dependence of kinetics for the ET from Cyt c to C c O. We identified that ∼20 water molecules were dehydrated in complex formation under turnover conditions, and systematic Cyt c mutations in the interaction site for C c O revealed that nearly half of the released hydration water during the complexation were located around Ile81, one of the hydrophobic amino acid residues near the exposed heme periphery of Cyt c . Such a dehydration dominantly compensates for the entropy decrease due to the association of Cyt c with C c O, resulting in the entropy-driven ET reaction. The energetic analysis of the interprotein interactions in the ET complex predicted by the docking simulation suggested the formation of hydrophobic interaction sites surrounding the exposed heme periphery of Cyt c in the Cyt c –C c O interface (a 'molecular breakwater'). Such sites would contribute to the formation of the hydrophobic ET pathway from Cyt c to C c O by blocking water access from the bulk water phase.